Referendum study 2003 - Holmberg, Sören; Ekengren Oscarsson, Henrik; Statistics Sweden (University of Gothenburg, 2005)
In conjunction with the referendum on Swedish membership of the European monetary Union (EMU) an election study was carried out in collaboration between Statistics Sweden and the Department of Political Science at Göteborg University.

Purpose:

Explain why people vote as they do and why an election ends in a particular way. Track and follow trends in the Swedish electoral democracy and make comparisons with other countries.

In conjunction with the referendum on Swedish membership of the European monetary Union (EMU) an election study was carried out in collaboration between Statistics Sweden and the Department of Political Science at Göteborg University.

Syfte:

Förklara varför väljare röstar som de gör och varför val slutar som de gör. Spåra och följa trender i svensk valdemokrati och göra jämförelser med utvecklingen i andra länder.
Folkomröstningsundersökningen 2003
FU03
Keywords: elections; val; european union; europeiska unionen; european integration; europeisk integration; referendums; folkomröstningar; single european currency; gemensam europeisk valuta; electoral issues; valfrågor; Political behaviour and attitudes; Politiska beteenden och attityder; Elections; Val; Government, political systems and organisations; Regering, politiska system och organisationer; International politics and organisations; Internationell politik och organisationer; Social Sciences; Samhällsvetenskap; Political Science; Statsvetenskap